The Impact of Profitability and Capital Structure on Firm Value of KBMI 4 Banks during 2020–2024 - Dafa Rakha Wijdan; Soritaon Soritaon; Farid Arifin (Business Management, 2026)
This study aims to analyze the effect of profitability and capital structure on firm value in KBMI 4 banks during the 2020-2024 period. The study uses a quantitative explanatory approach with panel data derived from the annual financial statements of PT Bank Central Asia Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, and PT Bank Negara Indonesia (Persero) Tbk. Profitability is proxied by Return on Assets (ROA), capital structure is proxied by Debt to Equity Ratio (DER), and firm value is proxied by Price to Book Value (PBV). Data collection techniques use documentation and literature study. The planned data analysis includes descriptive statistics, classical assumption tests, multiple linear regression, t test, F test, and coefficient of determination. The background of this study is the inconsistency between theory and empirical phenomena in KBMI 4 banks, where an increase in profitability is not always followed by an increase in firm value, and changes in capital structure receive different responses from the market. This study is expected to provide empirical evidence regarding the role of profitability and capital structure in shaping firm value in large banking companies in Indonesia.